Effects of coadministration of DHA and vitamin E on spermatogram, seminal oxidative stress, and sperm phospholipids in asthenozoospermic men: a randomized controlled trial. Issue 3 (26th May 2020) - Eslamian, Ghazaleh; Amirjannati, Naser; Noori, Nazanin; Sadeghi, Mohammad-Reza; Hekmatdoost, Azita
ABSTRACT: Background: It is unknown which compounds in spermatozoa or seminal plasma may be involved in the regulation of sperm motility. Objectives: The aim of this study was to investigate the effects of DHA (22:6n–3), vitamin E, and their probable interactions in men with asthenozoospermia. Methods: A factorial, randomized, double-blind, placebo-controlled trial was conducted in infertility clinics in Tehran, Iran. The participants were idiopathic asthenozoospermic men aged 20–45 y, with normal endocrine function. Their concentration of spermatozoa and percentage of morphologically normal spermatozoa were equal to or above the lower reference limits, according to the fifth edition of the WHO guideline. Out of 717 men referred to the infertility clinics, 180 asthenozoospermic men were randomly assigned to 1 of 4 groups according to stratified blocked randomization by age and sperm concentration. Participants took daily 465 mg DHA plus 600 IU vitamin E (DE), 465 mg DHA plus placebo (DP), 600 IU vitamin E plus placebo (EP), or both placebo capsules (PP) for 12 wk. Sperm characteristics, oxidative stress of seminal plasma, serum and sperm membrane fatty acids, dietary intakes, anthropometric measurements, and physical activity were measured at baseline and after 12 wk. Results: After the intervention, mean ± SD sperm progressive motility was greater in the DE group (27.9 ± 2.8) than in the DP (25.7 ± 3.4), EP (26.1 ± 2.8), and PP (25.8 ± 2.6) groups ( P < 0.05). Sperm count ( P = 0.001) and concentration ( P = 0.044) increased significantly in the DE group compared with the other 3 groups, whereas other semen parameters were not significantly different between the groups after the intervention. Serum concentrations of n–3 PUFAs were significantly higher in the DE and DP groups than in the EP and PP groups. Conclusions: Combined DHA and vitamin E supplements led to increased sperm motility; however, no significant changes occurred in sperm morphology and vitality in asthenozoospermic men. This trial was registered at clinicaltrials.gov as NCT01846325.